Implementasi Kurikulum 2013 di Sekolah Indonesia Deen Haag Belanda dan Sekolah Indonesia Kuala Lumpur Malaysia - Husni Mubarok; Indun Rohmaedah; Anni Qurrotul Aini; Wahyu Aditya Rahmawati; Sinta Mahanani; Riska Yustiani (Pendidikan Agama Islam STIT Palapa Nusantara, 2021)
The implementation of the 2013 curriculum is expected to be able to produce productive, creative, and innovative students to compete in the international world. This study aims to determine the implementation of the 2013 curriculum at the Dutch Indonesian School in The Hague (SIDH) and the Kuala Lumpur Indonesia School (SIKL) Malaysia. The method used in this research is qualitative method. Data collection was carried out through interview techniques and literature studies. The results showed that the Dutch School of Indonesia in The Hague (SIDH) also fully implemented the curriculum in accordance with the national curriculum standards in Indonesia. The application of the learning curriculum at the Dutch Indonesian School in The Hague (SIDH) is similar to schools in Indonesia. The Dutch School of Indonesia in The Hague (SIDH) has a challenge, namely the emphasis on the values ​​of nationalism and religious character. Meanwhile, Sekolah Indonesia Kuala Lumpur (SIKL) Malaysia applies a curriculum called the Living Curriculum. The Living Curriculum was formed with the aim of combining or empowering family, community, and school education with one scope. This Living Curriculum is applied so that students have character and have life skills that do not only refer to knowledge. Students are expected to be able to recount learning at home with their parents. With the implementation of the curriculum, students are expected to have character and life skills that are embedded in them.